2013
DOI: 10.1523/jneurosci.0886-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Mediates Neuroprotection and Anti-Inflammatory Effects during EAE through ER  Signaling on Astrocytes But Not through ER  Signaling on Astrocytes or Neurons

Abstract: Estrogens can signal through either estrogen receptor ␣ (ER␣) or ␤ (ER␤) to ameliorate experimental autoimmune encephalomyelitis (EAE), the most widely used mouse model of multiple sclerosis (MS). Cellular targets of estrogen-mediated neuroprotection are still being elucidated. Previously, we demonstrated that ER␣ on astrocytes, but not neurons, was critical for ER␣ ligand-mediated neuroprotection in EAE, including decreased T-cell and macrophage inflammation and decreased axonal loss. Here, we determined whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
124
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(132 citation statements)
references
References 62 publications
5
124
1
2
Order By: Relevance
“…For example, expression of structural filaments, such as GFAP or vimentin can be induced by signaling pathways associated with cAMP, STAT3, NF-kB, Rho-kinase, JNK, calci- (Brambilla et al 2005(Brambilla et al , 2009Okada et al 2006). Deletion of estrogen receptor-a, but not estrogen receptor-b, selectively from astrocytes diminishes the antiinflammatory and neuroprotective effects of estrogen on autoimmune inflammation (Spence et al 2011(Spence et al , 2013. In contrast, deletion of STAT3 or its associated membrane receptor GP130, markedly increases the spread of inflammation after traumatic injury, autoimmune disease, or infection (Okada et al 2006;Drogemuller et al 2008;Herrmann et al 2008;Haroon et al 2011;Wanner et al 2013).…”
Section: Selective Regulation Of Specific Functions and Effects Of Asmentioning
confidence: 99%
“…For example, expression of structural filaments, such as GFAP or vimentin can be induced by signaling pathways associated with cAMP, STAT3, NF-kB, Rho-kinase, JNK, calci- (Brambilla et al 2005(Brambilla et al , 2009Okada et al 2006). Deletion of estrogen receptor-a, but not estrogen receptor-b, selectively from astrocytes diminishes the antiinflammatory and neuroprotective effects of estrogen on autoimmune inflammation (Spence et al 2011(Spence et al , 2013. In contrast, deletion of STAT3 or its associated membrane receptor GP130, markedly increases the spread of inflammation after traumatic injury, autoimmune disease, or infection (Okada et al 2006;Drogemuller et al 2008;Herrmann et al 2008;Haroon et al 2011;Wanner et al 2013).…”
Section: Selective Regulation Of Specific Functions and Effects Of Asmentioning
confidence: 99%
“…[29,73] Moreover, using conditional ERβ knock-out mouse models, it was reported that DPN-conferred neuroprotection was not dependent on ERβ-signaling in astrocytes nor in neurons, suggesting a role for oligodendrocytes as the primary targets of this ERβ ligand. [74] Indeed, DPN was shown to act through ERβ-signaling in oligodendrocytes not only to prevent demyelination, but also to promote remyelination. [75] Thus, it has been proposed that such ERβ-ligands could be used in combination with anti-inflammatory drugs in MS patients.…”
Section: Evidence For E2 Direct Action On Central Nervous System-resimentioning
confidence: 99%
“…It has been shown that administration of E2 or ERα-specific agonists in mice during the chronic phase of active EAE was able to inhibit the expression of inflammatory chemokines CCL2 and CCL7 by astrocytes in vivo. [30,74] Using conditional knock-out mice, Spence et al showed that this neuroprotective action was mediated through ERα-signaling in astrocytes. [31,74] Altogether, these observations suggest that differences in ER-specific ligands are not only the result of distinct pharmacological effects, but that each ligand may have different cellular targets.…”
Section: Evidence For E2 Direct Action On Central Nervous System-resimentioning
confidence: 99%
See 2 more Smart Citations